Trudne związki katolickiej nauki społecznej i ekonomii - Klimczak, Bożena (Annales. Etyka w Życiu Gospodarczym, 2012)
The paper discuss the early age of forming social and economic catholic teaching in XIV–XVI. Appearing of economy from the area of theology was discussed as phenomenon of school from Salamanca and the influence scholastic on Adam Smith. The separation of economy and theology on the contrary was discussed as phenomenon of liberal project of state and market economy. The conclusion is, that economics as a science of separated aspects of human life is a subsidiary discipline of social catholic teaching.